Clinical Pharmacist’s knowledge of general anesthesia and drugs used to anesthetize patients with hypertension in Saudi Arabia, 2024 - Mansour Al Shehaiwin; Abdulaziz Nafea Alrashdi; Hassan Mahja Hassan Albalawi; Raed Mohammed Alrajhi; Albaraa Mohammad Alwafi; Fahd Mohammed Al-Asimi; Nahed Abdulrahman Al-Qwaiz; Mothkir Abdullah Al-Maqati; Shada Mahmoud Abujabal; Abdullah Lahq Shlyoih Alotaibi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The integration of the pharmacist in the care pathway could optimize patient information regarding the correct use of analgesics, communication in the multi-professional team, community-hospital coordination, and patient adherence to the prescribed medications, so that patients become more engaged in their care.In addition to enforcing pharmaceutical safety regulations, pharmacists are required to play significant roles as members of various perioperative care teams. Their responsibilities also include optimizing drug therapy and other clinical interventions. However, it would be beneficial to include general perioperative management in pharmaceutical education since it is another essential function that operating room pharmacists perform. Enhancing the perioperative care that pharmacists offer can help to raise their level of clinical competency. The study aimed: To assess the pharmacist’s knowledge of general anesthesia and drugs used to anesthetize patients who suffer from hypertension. Materials and Methods: A cross-sectional study was conducted in Makkah, Saudi Arabia. A self-designed questionnaire was distributed to 100 pharmacists. Results: The study discovered that 36.0% of the pharmacists were aware that sodium nitroprusside is used to regulate blood pressure during the procedure, that over half of them had rudimentary knowledge of the medications used in anesthesia, and that their knowledge of the medications used to treat hypertension during surgery was lacking. Conclusion: According to this study, a significant portion of the pharmacist participants’ knowledge was inaccurate due to their weaknesses. These shortcomings could result from inadequate training or inadequate educational preparation prior to the pharmacists’ employment in hospitals.